Microplastics elutriation system. Part A: Numerical modeling. Issue 2 (30th June 2017) - Kedzierski, Mikaël; Le Tilly, Véronique; Bourseau, Patrick; Bellegou, Hervé; César, Guy; Sire, Olivier; Bruzaud, Stéphane
Abstract: The elutriation process has shown its efficiency to extract microplastics from sand and began to spread in the scientific community. This extraction technic requires knowing with accuracy the extraction velocities of particles. This study aims to test whether numerical modeling could help to calculate these velocities. From hydrodynamic equations, a numerical model has been developed and the outputs are compared to experimental extraction data. The results show, for the calculated velocities, the experimental plastic extraction yields will be higher than 90% for < 10% of sand contamination. The model also allows determining that, with the actual protocol, the maximum plastic density which can be extracted is about 1450 kg·m − 3 whereas the detrimental resuspension, which may occur during the column filling step, is highlighted. From model calculations, it arises that changes in the column dimensioning and the protocol operations need to be considered. Highlights: The elutriation column is one of the best tools currently available for extracting plastics from sand. Developing a system using the elutriation technic is a scientific and technical issue. A numerical approach has been developed for optimizing the elutriation efficiency. The fluid velocity and the influence of the particle density and shape have been studied. This modeling allows designing the column dimensioning and adjusting the parameter setting.